In vitro replication competence of a hepatitis B genotype D/A recombinant virus: Dissimilar biological behaviour regarding its parental genotypes - Trinks, Julieta (2013)
Hepatitis B virus (HBV) DNA recombinants contribute to ~30% of the overall full-length sequences already deposited in GenBank. However, their biological behaviour has not been analysed so far. In this study, the in vitro replication kinetics of the first D/A recombinant from the American continent differed from its parental genotypes, exhibiting higher extracellular levels of HBV DNA and hepatitis B e antigen. Southern blots of intracellular core-associated HBV DNA were in agreement with such results. Because this recombinant was obtained from an Argentinian injecting drug user belonging to a vulnerable community, these results are of singular relevance for regional public health. Further in vivo studies are urgently needed to determine the pathogenicity of these replicative competent clones.